2022
DOI: 10.1111/jocn.16219
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review: Treatment attitudes and adherence for adults with schizophrenia

Abstract: Aim and objectives This scoping review presents an exploration of literature on the relationship between treatment attitudes and adherence in adults experiencing schizophrenia. Background Strategies to address adherence and improve treatment outcomes are described in literature. However, adherence remains a challenge for people experiencing mental illness in practice. Transformational frameworks, evidence‐based practice and patient‐centred approaches have been established and implemented but non‐adherence inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…In this study, the respondents who suffered from side effects of the drugs are more likely to be non-adherence to medication. The side effects of the drug cause the patients to feel drowsiness, headache, and movement problem [14]. The study also reported that participants did not have adequate support from families.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, the respondents who suffered from side effects of the drugs are more likely to be non-adherence to medication. The side effects of the drug cause the patients to feel drowsiness, headache, and movement problem [14]. The study also reported that participants did not have adequate support from families.…”
Section: Discussionmentioning
confidence: 92%
“…In all analyzed studies, the process of adherence is dynamic rather than static, involving objective and subjective personal experiences characterized by the ability to establish interpersonal skills [33]. At the individual level, this process includes the patient's readiness to change and motivation for mental health treatment [34][35][36][37], their medication literacy (readiness to understand the role of medication, how to use it, what works for each person, ability to reflect on past experiences and its effects) [3,34,36,[38][39][40], illness/symptom experience [41][42][43], coping and interpersonal skills [33,44], self-care ability [33,43], and self-efficacy [36,37,45].…”
Section: Attributesmentioning
confidence: 99%
“…(a) Family involvement and social support [39,40,48,51,58]; (b) Patient and family ongoing support [42,48,61]; (c) Mutual support groups [46,59,60];…”
Section: Community Support Containsmentioning
confidence: 99%
“…Wen-Ling Hsieh 1,2 | I-Hsien Li 1,3 | Wen-I Liu 1 recovery of individuals' disease process (Caqueo-Urízar et al, 2021;Nyanyiwa et al, 2022;Pennington & McCrone, 2018;Vega et al, 2021).…”
Section: Effects Of Empowerment-based Illness Management On the Medic...mentioning
confidence: 99%
“…The clinical guidelines of the American Psychiatric Association indicate that pharmacotherapy is the treatment approach with the highest level of evidence in terms of effectiveness compared to other approaches (Keepers et al, 2020). However, medication adherence in persons may be interrupted by numerous factors, including symptom severity, side effects of drugs, medication attitude, insight, and support system, resulting in a non‐adherence rate of 58.2%, which is associated with high medical and social costs, affecting the progression and recovery of individuals' disease process (Caqueo‐Urízar et al, 2021; Nyanyiwa et al, 2022; Pennington & McCrone, 2018; Vega et al, 2021).…”
Section: Introductionmentioning
confidence: 99%